23: VASCULAR INFLAMMATION AND AORTIC WALL CHARACTERISTICS MODULATE FOLLOWING LIFESTYLE CHANGES IN PSORIASIS PATIENTS AT 1 YEAR FOLLOW UP. Issue 3 (23rd February 2016) - Joshi, A; Shukla, P; Aberra, TM; Lerman, JB; Natarajan, B; Ng, Q; Silverman, J; Rodante, J; Mehta, NN
Abstract : Purpose of Study: Psoriasis (PSO), a chronic inflammatory skin disease, is associated with increased CV risk and vascular inflammation (VI). However, the effect of therapeutic lifestyle changes (TLC) including exercise on VI over time is unknown. We hypothesized that TLC would lead to an improvement in VI at 1 year accompanied by improvements in aortic wall characteristics. Methods Used: 65 PSO patients, recruited consecutively, underwent FDG PET/CT, phase contrast MRI scans and clinical visits for evaluation of VI, wall characteristics and exercise frequency, at baseline and 1 year follow-up. VI was measured as Target-to-background ratio (TBR), and aortic distensibility (AD) and wall thickness were assessed by commercial software on phase contrast MRI scans. Clinical parameters were ascertained by both survey and provider. Summary of Results: VI decreased at 1 year (6.5% decrease in TBR; p<0.0001), and was inversely associated with exercise frequency beyond adjustment for CV risk factors (β=−0.27; p=0.001). Furthermore, this decrease in VI was associated with improvement in AD (40% increase; p<0.001) and aortic wall thickness (8.5% decrease; p<0.001). Conclusions: Our findings suggest that VI improves with TLC. This 6.5% decrease in VI could lead to ∼30% reduction in future adverse events, based on a recent large prospective study. This VI reduction is also associated with improved aortic wall characteristics suggesting that targeting VI as a surrogate marker holds promise to understand the effects of TLC on CV disease.Abstract 23 Figure 1